Seed Nanopriming and Nanosilica Combined with Field Capacity Treatments: Impacts on Chlorophyll and Morphological Traits of Inpari 32 HDB - Rika Rismayang; Ida Retno Moeljani; Rossyda Priyadarshini; Juli Santoso (Jurnal Penelitian Pendidikan IPA, 2025)
Drought stress can cause reduced rice production. One effort that can be made is seed nanopriming. This study aims to examine the effect of nanosilica seed nanopriming and field capacity on the chlorophyll content and morphological growth of the Inpari 32 HDB rice variety. The study was designed using a completely randomized factorial design with two factors, namely nanosilica concentration (0, 600, 900, and 1,200 mg/L) and field capacity (3 cm, 100%, 75%, and 50% flooding). The results showed that the treatment combinations produced different responses in physiological and morphological parameters. Chlorophyll content increased with increasing nanosilica concentration, with the highest value found in the treatment with 1,200 mg/L of nanosilica and 3-cm flooding. Plant height and leaf width parameters did not show significant differences, but there was a tendency for better growth at higher nanosilica concentrations. For root length and root wet weight parameters, a very significant interaction was found, where the 1,200 mg/L of nanosilica treatment under flooding conditions produced the longest roots and the highest root biomass. Conversely, a 50% field capacity caused a significant decrease in all observed parameters. Overall, nanosilica seed nanopriming, especially at a concentration of 1,200 mg/L, can increase rice tolerance to drought stress by increasing chlorophyll content, root growth, and root biomass.